Predicting the Relapse of Hyperthyroidism in Treated Graves’ Disease with Orbitopathy by Serial Measurements of TSH-Receptor Autoantibodies - Stöhr, Mareile; Oeverhaus, Michael; Lytton, Simon D.; Horstmann, Mareike; Zwanziger, Denise; Möller, Lars; Stark, Achim; Führer-Sakel, Dagmar; Bechrakis, Nikolaos; Berchner-Pfannschmidt, Utta; Banga, J. Paul; Philipp, Svenja; Eckstein, Anja (Hormone and Metabolic Research, 2021)
The aim of this study was to investigate the potential of the new TSH-receptor antibody (TRAb) assays to predict remission or relapse of hyperthyroidism in patients with Graves’ disease (GD) and Graves’ orbitopathy (GO). TRAbs were measured retrospectively in sera from a cohort of GD patients with GO (n=117; remission n=38 and relapse n=79–Essen GO biobank) with automated binding immunoassays: TRAb Elecsys (Cobas Roche) and TRAb bridge assay (IMMULITE, Siemens), and the TSAb (thyroid stimulating Ab) cell-based bioassay (Thyretain, Quidel Corp.). To identify relapse risk/remission of hyperthyroidism patients were followed up at least 10 months after the end of antithyroid drug therapy (ATD) therapy. ROC plot analysis was performed to calculate cut-off levels of TRAb and TSAb for prediction of relapse and remission of hyperthyroidism. Cut-off serum levels are provided for timepoints around 3, 6, 10, and 15 months after the beginning of ATD. Repeated measurements of TRAb increase the rate of relapses predictions to 60% (Elecsys), 70% (IMMULITE), and 55% (Thyretain). Patients with remission have consistently TRAb levels below the cut off for relapse in repeated measurements. The cell-based bioassay was the most sensitive – and continued to be positive during follow up [at 15 months: 90% vs. 70% (IMMULITE) and 65% (Elecsys)]. Identification of relapsing hyperthyroidism is possible with automated immunoassays and cell-based bioassay especially with serial TRAb measurements during the course of ATD therapy. Patient who need eye surgery may profit from an early decision towards definitive treatment.
Keywords: binding assays; bioassays; TSH receptor antibodies; TRAb; Graves’ disease; Graves’ orbitopathy